Dramawebben - Lagercrantz, Marika; Lindgren, Ulrika (Riksteatern, 2012)
Dramawebben started in 2006 as a project at Nationella dramaturgiatet. The aim of the project was to make copyright free Swedish drama written by women freely available. The project received further funding from Riksbankens jubileumsfond 2009-2012. The goal was to develop the existing piece directory to a "non-commercial web site for copyright free drama". In December 2009, www.dramawebben.se was launched with a new database, a new web platform and interfaces corresponding with content, activities and user groups. The work of the project has aimed to build a usable and sustainable infrastructure for research and teaching. Each stage in the process of collecting, processing and publishing the materials have been designed in preparation for research, corresponding to the development of Dramawebben as an infrastructure for digital humanities research. The work of collecting materials, cataloging and publishing has been guided by a gender perspective. Since its inception, a form of descriptive catalog records has developed in the project where the content of the play and the reception at the first performance are summarized. Drama texts have been published in two formats, "facsimile" and "processable text"'. The descriptive catalog contains about 500 pieces from 1600 to modern times (2012). The drama is mainly taken from the following archives: the Royal Dramatic Theatre's archives, Royal theaters Archive, Music and Theatre Library, National Library, Society of Swedish Literature in Finland and the Swedish institute for children's books.Through infrastructure funding by the Swedish Research Council 2012-2014, the texts will be encoded with specific information to enable machine searches for research on cross-cutting structures and relationships within Swedish drama.

Purpose:

The purpose of Dramawebben is creating a digital piece archive of copyright-free Swedish drama. The drama is freely available at no cost to users to read online or download for process. The drama texts are reproduced in fulltext and are published either in the so-called facsimile, a PDF document where the original print is rendered as a digital photocopy, or processable text, a PDF document with text and image that can be used for editing. By making the digital piece archive freely available, Dramawebben brings Swedish drama up to date.

Dramawebben startade 2006 som ett accessprojekt inom Nationella dramaturgiatet. Uppdraget var att tillgängliggöra upphovsrättsligt fri svensk dramatik skriven av kvinnor. Projektet erhöll infrastrukturstöd från Riksbankens Jubileumsfond för åren 2009-2012. Målet var att utveckla den befintliga pjäskatalogen till en "icke-kommersiell portal för upphovsrättsligt fri dramatik". I december 2009 lanserades www.dramawebben.se med en ny databas, en ny webbplattform och gränssnitt i paritet med innehåll, verksamhet och användargrupper. Arbetet i projektet har syftat till att bygga upp en användbar och hållbar infrastruktur för forskning och undervisning. Varje moment i arbetet med att samla in, förädla och publicera materialet har utformats för att lägga en forskningsförberedande grund som håller för en utveckling av Dramawebben som infrastruktur för digital humanistisk forskning. Arbetet med insamling av material, katalogisering och publicering har från början styrts av ett genusperspektiv. Sedan starten har en form för beskrivande katalogposter utvecklats i projektet där handlingen i pjäsen och mottagandet vid urpremiären sammanfattats. Dramatexterna har publicerats i två olika format, "faksimil" och "bearbetningsbar text". 2011 innehåller den beskrivande katalogen ca 500 pjäser från 1600-talet till modern tid. Dramatiken är huvudsakligen hämtad från följande arkiv: Kungliga Dramatiska Teaterns arkiv, Kungliga teatrarnas arkiv, Musik- och teaterbiblioteket, Kungliga biblioteket, Svenska Litteratursällskapet i Finland och Svenska barnboksinstitutet. Genom ett infrastrukturstöd från Vetenskapsrådet 2012- 2014, kommer texterna att kodas med specifik information för att möjliggöra maskinella sökningar för forskning om övergripande strukturer och förhållanden inom svensk dramatik.

Syfte:

Syftet med Dramawebben är att skapa ett digitalt pjäsarkiv över upphovsrättsligt fri svensk dramatik. Dramatiken är fritt tillgänglig utan kostnad för användarna att läsa på nätet eller att ladda ner för att bearbeta till spelmanus. Dramatexterna finns återgivna i fulltext och är publicerade antingen i sk faksimil, ett pdf-dokument där originaltrycket återges som en digital fotokopia, eller i bearbetningsbar text, ett pdf-dokument med text och bild som kan användas för redigering. Dramawebben växer i takt med att nya verk blir kända. Med det digitala pjäsmaterialet tillgängliggör och aktualiserar Dramawebben svensk dramatik.
Dramawebben
Keywords: languages; språk; gender; genus; 17th century; 1600-tal; 18th century; 1700-tal; 19th century; 1800-tal; 20th century; 1900-tal; 21st century; 2000-tal; drama texts; dramatexter; drama; dramatik; plays; pjäser; theatre; teater; texts; texter; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; General Literary studies; Litteraturvetenskap; Performing Art Studies; Teatervetenskap